Spectral broadening of a single Ce3+-doped garnet by chemical unit cosubstitution for near ultraviolet LED - Khan (Han) Tao; Lang Tianchun; Zhong Yang; Cao Shixiu; Peng Lingling; Yakovlev A. N. Aleksey Nikolaevich; Polisadova E. F. Elena Fyodorovna (2018, 2018)
Title screen